Exploring Challenges and Motivational Factors in Task-Based Language Teaching for Speaking Proficiency: Learning-Oriented Assessment - Kurniati, Tri Septiana; ., Margana; Nurhayati, Endang; Diani, Irma; Rahmat, Sujud Puji Nur; Tauchid, Ahmad (Journal of Cultural Analysis and Social Change, 2025)
This study explores the challenges and motivational factors influencing non-English major students' engagement in task-based language teaching (TBLT) within ESP speaking courses, highlighting the significance of learning-oriented assessment (LOA). While TBLT has been recognized for promoting communicative competence, learner autonomy, and classroom interaction, understanding students’ personal experiences and the role of assessment strategies remains crucial for enhancing learning outcomes. The research aims to examine how students utilize LOA strategies such as feedback, peer collaboration, and self-reflection to overcome language learning challenges and sustain motivation. Adopting a qualitative, phenomenological approach, data were collected through face-to-face interviews with 25 undergraduate students enrolled in ESP courses at an Indonesian university. Thematic analysis supported by NVivo software was used for data interpretation. Results indicate students face linguistic, emotional, and cognitive challenges, but engagement with LOA practices helps foster confidence and improves speaking performance. The findings emphasize the importance of integrating formative assessment practices tailored to learners’ needs within TBLT to promote motivation and effective language development. These insights provide valuable implications for designing student-centered ESP instruction that actively supports learners’ communicative and motivational growth.